Peran Kepemimpinan Kepala Sekolah Perempuan Terhadap Pembinaan Akhlak di Sekolah Dasar - Wasito; Siti Aishah; Alivia Wulan (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
This study discusses the leadership role of female principals towards moral development in elementary schools in learning, especially moral creed. Principals are required to have the ability to influence their subordinates, which means leadership is a process of influencing a person or group to want to carry out their duties voluntarily so as to achieve the goals of the institution that oversees it. The principal is one of the most important roles in an educational institution, because the principal is the main driving force in every educational activity, with the hope of improving the quality of the educational institution he leads. This study aims to determine the leadership style, leadership strategies of female principals in developing the quality of education in schools. Leadership is an attitude of influencing others to achieve a goal. Leadership is always synonymous with the role of a man even in the world of education. But along with the times women also have equal rights and abilities. Female madrasah principals are able to balance men in leading an educational institution so that the institution has good quality and can compete in the market. Keywords: Leadership Role; Principal; Women; Moral Development